Peningkatan keterampilan menulis narasi melalui model pembelajaran kooperatif tipe roundtable pada peserta didik kelas iii sekolah dasar - Rahayu, Isnaini Suci; Suharno, Suharno; Hadiyah, Hadiyah (Universitas Sebelas Maret, 2020)
The purpose of this study is to improve the narrative text writing skills used Roundtable. This study is a Classroom Action Study (CAR) with two cycles. The subject is the student of state Elementary School Bulukantil in academic year 2018/2019 with 40 students. The data collection techniques of this study used observation, interviews, documentation, and test.The validity of data using source triangulation and technical triangulation. This study used an interactive analysis from miles-Huberman data analysis. The initial condition of narrative text writing skills of grade III students resuled in 27,5% classically. The first cylce begins with first meeting of 55% in classical. The second begins with first meeting of 87.5% classical completeness. The conclusions in this study is roundtable improved narrative writing skills on students at grade III of state Elementary School Bulukantil 2018/2019 academic year.